2021
DOI: 10.1021/acsami.1c16680
|View full text |Cite
|
Sign up to set email alerts
|

Irregular Wind Energy Harvesting by a Turbine Vent Triboelectric Nanogenerator and Its Application in a Self-Powered On-Site Industrial Monitoring System

Abstract: Wind is a regenerative and sustainable green energy, but it is intermittent; especially, harvesting irregular wind energy is a great challenge for existing technologies. This study demonstrates a turbine vent triboelectric nanogenerator (TV-TENG), which can be utilized as both an irregular wind harvester and a self-powered environmental sensing system on the rooftops of buildings. At a wind speed of nearly 7 m/s, the TV-TENG delivers an open-circuit voltage of up to 178.2 V, a short-circuit current of 38.2 μA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…In addition to TENG for heat recovery, it is reported that TENG can also be used for self-powered modern industrial monitoring. Zhang et al designed a turbine vent TENG (TV-TENG) on the roof of buildings to harvest irregular wind energy for self-powered environmental sensing system [ 81 ]. On the one hand, TV-TENG collects irregular wind energy in the environment for power supply of low-power sensors and other related microelectronic devices in industrial production.…”
Section: Teng Applications In Smart Industrymentioning
confidence: 99%
“…In addition to TENG for heat recovery, it is reported that TENG can also be used for self-powered modern industrial monitoring. Zhang et al designed a turbine vent TENG (TV-TENG) on the roof of buildings to harvest irregular wind energy for self-powered environmental sensing system [ 81 ]. On the one hand, TV-TENG collects irregular wind energy in the environment for power supply of low-power sensors and other related microelectronic devices in industrial production.…”
Section: Teng Applications In Smart Industrymentioning
confidence: 99%
“…Triboelectric nanogenerator (TENG), originating from the coupling effect of triboelectrification and electrostatic induction, is proved to be a cost-effective and eco-friendly technology to convert irregular mechanical energy into electrical energy, [20][21][22][23][24] especially for low frequency vibrational energy such as wind and wave energy. [25][26][27][28][29] Furthermore, the high open-circuit voltage is one typical characteristic of TENG, which can reach several thousand volts easily, [30][31][32] hence it is promising for removing PM from the atmospheric pollution using electrostatic effects. [33] In this work, a practical and economical self-powered highvoltage recharging system is proposed for removing tobacco smoke in the air.…”
Section: Research Articlementioning
confidence: 99%
“…A turbine vent shell made of 304 stainless steel is attached to the top of the smoking room and this construction has been proved to be very waterproof in our previous work. [34] The photograph of the internal structure is illustrated in Figure S1, Supporting Information. The turbine unit contains a self-powered high-voltage recharging system inside as shown in Figure 1b.…”
Section: Structure and Working Principlementioning
confidence: 99%
“…35 Besides, the performance of TENGs can also be improved based on the dielectric enhancement effect and the new structures. [36][37][38][39][40][41][42][43] Because TENGs have the advantages of small size, portability, and especially high output, they are suitable for building self-powered devices or systems. 44,45 Hence, the self-powered ACEL devices based on TENGs have tremendous potential in wearable devices and flexible displays, however little work has been conducted in this regard.…”
Section: Introductionmentioning
confidence: 99%